Evaluation of Three Deworming Methods and their Long-Term Effect on the Weight of Buffaloes Raised in Silvopastoral Systems - Chacón-Condori, Efraín; Díaz, Wimar; Sonabi, Carlos; Hinojosa, Jorge; de la Cruz-Cruz, Luis Alberto; Berdugo-Gutiérrez, Jesús Alfredo (Journal of Buffalo Science, 2023)
Purpose of the Study: The present work aimed to evaluate the effect of three deworming methods on body weight gains in buffaloes raised in silvopastoral systems (SPS). Methods: Thirty buffaloes were divided into three groups (ten per group) as follows: 1) Albendazole 10 g + 1.3 g of cobalt sulfate at one week of age and 14 days later; 2) Albendazole 10 g + 1.3 g of cobalt sulfate at one week of age and 14 days later, then at 6 months and 14 days later; 3) Ivermectin 1 g at 30 days of age and then at six months of age. Birth, weaning (9 months), and final (18 months) weight were registered, and daily weight gains were calculated. The McMaster technique was used to evaluate the presence of parasites. Results: The overall prevalence of parasites in the animals evaluated was 93.33%. The most common parasites were: Strongylus sp., Neoascaris sp., Moniezia sp., and Eimeria sp. Before the application of the dewormers, initial values in G1, G2, and G3 were 360, 350, and 210 hpg/opg; after the application of the treatments, 60, 25, and 20 hpg/opg were obtained, respectively. Buffaloes in G2 showed significantly (P=0.046) high final weights (415.10±23.76 kg) compared to G1 (354.80±46.71 kg) but showed no difference with G3 (374.80±43.60k). Conclusion: It is concluded that albendazole at 10 g and a repeat at six months of age can be used in buffalo breeding in SPS, which could help to implement regenerative livestock programs, decreasing the use of Ivermectin.